2017
DOI: 10.1038/npp.2017.209
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and Preclinical Evidence for Functional Interactions of Cannabidiol and Δ9-Tetrahydrocannabinol

Abstract: The plant Cannabis sativa, commonly called cannabis or marijuana, has been used for its psychotropic and mind-altering side effects for millennia. There has been growing attention in recent years on its potential therapeutic efficacy as municipalities and legislative bodies in the United States, Canada, and other countries grapple with enacting policy to facilitate the use of cannabis or its constituents for medical purposes. There are >550 chemical compounds and >100 phytocannabinoids isolated from cannabis, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
173
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 192 publications
(179 citation statements)
references
References 146 publications
3
173
0
3
Order By: Relevance
“…Although THC is the primary cannabis constituent responsible for its harmful effects, CBD may offset some of these harms [15][16][17]. For example, some (but not all [44]) studies have reported that the acute effects of THC on verbal memory impairment [45,46] and psychotic-like symptoms [46,47] were partially offset when CBD was co-administered with THC.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although THC is the primary cannabis constituent responsible for its harmful effects, CBD may offset some of these harms [15][16][17]. For example, some (but not all [44]) studies have reported that the acute effects of THC on verbal memory impairment [45,46] and psychotic-like symptoms [46,47] were partially offset when CBD was co-administered with THC.…”
Section: Discussionmentioning
confidence: 99%
“…Resin is primarily imported to Europe from Morocco; however, it is also imported from Lebanon and Afghanistan and produced domestically within Europe [14]. Resin found in European markets has been reported to contain significant levels of cannabidiol (CBD), a non-intoxicating cannabinoid that may offset THC harms [15][16][17], and is typically absent from herbal cannabis. Traditional resin production methods often include a mixture of three plant chemotypes (THC-dominant, CBD-dominant, THC and CBD) found in landrace crops [18], such as Moroccan 'kif '.…”
Section: Introductionmentioning
confidence: 99%
“…Cannabidiol is one of the two most abundant cannabinoids in the C. sativa plantthe other being THC (Turner et al 2017). CBD does not have the same psychoactive effects as THC and may counteract some of its behavioural and cognitive effects when the two are coadministered (Colizzi & Bhattacharyya 2017;Boggs et al 2018a). However, it may not be completely accurate to describe CBD as being 'non-psychoactive' or 'non-psychotropic', as there is emerging evidence it can elicit beneficial psychological effects in relation to anxiety, depression and schizophrenia (Russo 2017).…”
Section: What Is Cannabidiol (Cbd)?mentioning
confidence: 99%
“…Cannabidiol was first identified in 1940 by extraction of wild hemp grown in the US state of Minnesota (Adams et al 1940); its specific structure and stereochemistry were determined later in the 1960s (Boggs et al 2018a). Pure CBD is a white crystalline solid (molecular formula C 21 H 20 O 2 ) with a melting point of 62-63°C and is lipid soluble, as are other types of phytocannabinoids (WHO 2018).…”
Section: What Is Cannabidiol (Cbd)?mentioning
confidence: 99%
“…Inhalation of smoke from combusted cannabis exposes the lungs to pharmacologically active ingredients, such as tetrahydrocannabinol (THC) and cannabidiol (CBD), as well as combustion products such as polycyclic aromatic hydrocarbons that are shared with biomass exposures, including tobacco (30). The psychoactive and immunomodulatory effects of cannabis have historically been attributed to THC and CBD, respectively, although an increasing body of evidence suggests complex interactions between the two (31)(32)(33)(34). Habitual cannabis smoke exposure is associated with higher incidence of coughing, wheezing, chest tightness, and shortness of breath relative to non-smokers (20,(25)(26)(27)(28); symptoms that are shared with tobacco smoking despite the difference in chemical composition.…”
Section: Introductionmentioning
confidence: 99%